Décolonisation et affirmation autochtone dans les pratiques de collectionnement dans les musées - Eshrāghi, Léuli; Genest, Isabelle; Nepton Hotte, Caroline (Muséologies, 2026)
This article falls within the scope of reflection on the decolonization of Canadian museums, in accordance with the 2022 report of the Canadian Museums Association (CMA), which responds to the Truth and Reconciliation Commission of Canada’s Call to Action 67. The article represents a collaborative effort between a professor, an Ilnu museologist and a non-binary Indigenous curator, guided by an Indigenous methodological approach foregrounding reciprocity, orality and the plurality of voices. Together, the authors present two contrasting but complementary case studies: on the one hand, the Montreal Museum of Fine Arts (MMFA), a major institution undergoing transformation, and on the other, the Ilnu Museum of Mashteuiatsh, rooted in an Indigenous community approach since its creation in 1983.The concepts mobilized in this article are decolonization, empowerment and museum self-governance. The authors raise the issue of the colonial character of museums and the challenges of decolonizing their apparatus, with all that this evokes. A central criticism is the use of the word «object» in Western museology, which disconnects museum contents from their living, relational role in Indigenous cultures. Instead, the authors prefer to speak of «belongings,» a concept that encompasses the attached memory, relational aspect and sacredness of these elements.The aim of this work is to explore the decolonization of museums and the expression of genuine Indigenous sovereignty in the museum through two exemplary cases. It calls into question the actual capacity of museum institutions to integrate Indigenous knowledge in a profound and respectful way that moves beyond stated intentions. It also demonstrates the limits of museum decolonization without the real empowerment of Indigenous institutions, which must (re)construct the foundations of a museology rooted in community values. The article looks back at recent events, such as Wanda Nanibush’s controversial departure from the Art Gallery of Ontario, to illustrate the concrete limits of Indigenous inclusion in major cultural structures. The three authors call for a structural transformation of institutions, including a sincere recognition of Indigenous cultural sovereignty. Decolonization cannot be reduced to metaphor or symbolic gestures; it must be embodied in sustainable practices, backed by resources, human support and real political will. This is the only way museums can become places where knowledge can be co-constructed and passed on, and where ancestral ties can be reactivated.